Making a Market: Infrastructure, Integration and the Rise of Innovation - David Andersson; Thor Berger; Erik Prawitz (Research Institute of Industrial Economics (IFN), 2020)
We exploit exogenous variation arising from the historical rollout of the Swedish railroad network across municipalities to identify the impacts of lowered interaction costs on innovative activity. A network connection led to a surge in local innovation due to an increased entry, productivity, and specialization of independent inventors. As the railroad network expanded, it further led to the emergence of a national market for ideas: inventors in connected areas began to develop ideas with applications outside the local economy, which were subsequently sold to firms along the network. Our findings suggest that the reduced interaction cost between firms, intermediaries, and inventors was a key driver of the historical emergence of a market for ideas.
Keywords: O30; N70; O33; 330; Technological Change; Infrastructure; Innovation